Effects of Computer Assisted Task Based Listening Learning on Ethiopian Students’ Listening skills development - Engliz Ketema Kereba (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
This paper examined effects of computer assisted task based listening learning (CATBLL) on students’ listening skills development. The participants were freshman students of Adama Science and Technology University in 2019/2020 academic year. The experimental group was treated with computer assisted task based listening skills instruction approach while conventional method was employed for control group. Teacher made tests and students’ self-reflection journal were the data collection instruments used in this study. For the analyses of numerical data, paired sample t-test and independent samples t-test were computed. Qualitative analyses were done for the data obtained through students’ self-reflection journal. Based on the findings, the proposed approach resulted in a strong and significant effect on students’ listening skills development. A statistically significant difference was confirmed between the experimental group and the control group in terms of their listening achievement score. The results of qualitative analyses depict that the majority of the students in computer assisted group showed positive feeling towards the approach; they also reflected that they relatively improved their listening skills. This implies that computer assisted task based listening skills learning approach appeared to facilitate individual learning, and increase students’ concentration. Thus, one can conclude that computer assisted task based listening skills learning approach facilitated students’ listening skills development than the conventional one. Hence, it is advised to incorporate CATBLL in English language education is valuable in the digital world